Front of pack labels enhance attention to nutrition information in novel and commercial brands. (October 2015) - Becker, Mark W.; Bello, Nora M.; Sundar, Raghav P.; Peltier, Chad; Bix, Laura
Abstract: Objectives: (1) To assess whether Front-of-Pack (FOP) nutrition labels garner attention more readily than more complete, mandated nutrition information (the Nutrition Facts Panel (NFP), required in the US), and (2) To determine whether label design characteristics, specifically, color coding and/or coding with facial icons, increase attention to the FOP label. Methods: In two experiments, we tracked the allocation of attention while participants ( n  = 125) viewed novel and commercial packages with varied FOP designs using a change detection methodology. Results: We found empirical evidence that FOP labels are attended more often, and earlier, than the currently mandated NFP, and that this benefit is due both to its placement on the front of the package and to the design characteristics of the FOP. Specifically, the use of color in FOPs increased attention to the label, but there was no evidence that coding information via facial icons impacted attention. Conclusions: Our work supports a growing body of evidence supporting the use of FOP labels to attract attention to nutritional information. Findings may be relevant to inform policy decisions on labeling standards.